(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the system of values, socio-philosophical essence of values, improvement of positive attitude of youth towards national and universal values, socio-pedagogical necessity of formation of axiological consciousness in youth in the process of improvement of civil society were investigated.